Annealing atmosphere effect on Ni states in the thermal-decomposed NiOx films for perovskite solar cell application. (20th August 2018) - Guo, Yuxiao; Yin, Xingtian; Liu, Jie; Yang, Yawei; Chen, Wei; Que, Meidan; Que, Wenxiu; Gao, Bowen
Abstract: NiOx films with different Ni states are prepared by decomposing the solution-derived Ni(OH)2 films in varies of atmospheres. All the NiOx films exhibit full coverage on the substrates with rough surfaces. Both the air annealing and O2 annealing result in similar film compositions, which are composed of NiO, Ni2 O3 and NiOOH. While additional metallic nickel is observed in the N2 -annealed sample, which is different from the pure NiO powders annealed in N2, indicating a complicated decomposition process of Ni(OH)2 in N2 atmosphere. The as-prepared NiOx films were employed as the hole transport layer of inverted planar perovskite solar cells. Owing to the existence of metallic nickel, an obvious performance degradation is observed for device based on the N2 -annealed sample. Finally, the champion power conversion efficiency (PCE) of 14.55% is achieved on the device based on the air-annealed NiOx film, which should be attributed to the slightly higher content of NiOOH compared to the O2 -annealed sample. Graphical abstract: Image 1